Experience influences kinematic motor synergies: an Uncontrolled manifold approach to simulated Nordic skiing. - Frayne, Devon H.; Norman-Gerum, Valerie T.; Howarth, Samuel J.; Brown, Stephen H.M. (Journal of Sports Sciences, 2024)
Motor synergies are defined as central nervous system mechanisms which adjust participating degrees of freedom to ensure dynamic stability (control) of certain performance variables and have been identified during many motor tasks. The potential for synergistic control of individual segments during full-body tasks is often overlooked. Thus, this study compared individual differences in the potential stabilization of multiple performance variables on the basis of experience during a full-body sport activity. Normalized time series of synergy indices from Uncontrolled Manifold analyses on experienced (n = 9) and inexperienced (n = 19) participants were analysed using statistical parametric mapping during simulated Nordic skiing. Regardless of experience, hand, upper arm, and whole-body centre of mass (COM) kinematics were found to be stabilized by kinematic motor synergies. Only experienced Nordic skiers stabilized trunk COM position at all, while trunk COM velocity was stabilized for a longer duration than inexperienced participants. However, inexperienced participants stabilized hand velocity for a greater duration overall and to a greater magnitude during early pull phase than the experienced skiers. That motor synergies for hand and trunk COM velocity differed between experience groups suggests potential utility for these performance variables as indicators of motor skill development for full-body tasks such as Nordic skiing.